The Link Between from Day to Day Change of Weather Types and Synoptic Situations in Kraków During the Period 1961–2010 - Piotrowicz, Katarzyna; Szlagor, Joanna (Quaestiones Geographicae, 2013)
This paper analyses day-to-day changes of weather types and links these with synoptic situations, i.e. circulation types, air masses and weather fronts. The weather types were classified according to Woś (1999), while a calendar proposed by Niedźwiedź (2013) was used for synoptic situations. Weather records from Kraków were used covering the period 1961-2010. The frequency of all combinations of day-to-day weather type changes was calculated, identified using specific values of air temperature, cloudiness and precipitation. The analysis of the succession and frequency of the day-to-day changes was linked with the synoptic situations accompanying the change. It was found that the thermal weather types were relatively very stable and remained unchanged on the following day in 61.3% of cases, and that the synoptic situation also remained similar. Weather subtypes, identified with just cloudiness and precipitation, but not temperature, displayed much more day-to-day change in terms of frequency and scale. Synoptically it was the air mass change and/or the occurrence of atmospheric fronts, which tended to cause day-to-day weather type changes, while the impact of circulation was not always clear. Particular attention was devoted to sudden weather type changes caused primarily by dramatic air temperature fluctuations.